Proceduralism and integrativeness in public discussion - Pinter, Andrej (Javnost-The Public, 2004)
The article presents a critical analysis of proceduralist theories of deliberative democracy, which are built on the notion of public discussion as a fair procedure. Advocates of this idea -- Habermas, Rawls, Cohen, Estlund and others -- claim that the rational transformation of opinions in discussions grants legitimacy to democratic decision-making. In this respect, they enter the domain of communication studies. Thus, does proceduralism assume social integration or contribute to it? The question is operationalised with the notions of power and universalism. It turns out that public discussion as a democratic procedure enables contact between incommensurable forms of power. This is achieved by consenting to a democratic procedure, if it does not lead to additional homogenisation. It is argued that to save proceduralism from a critique of its impartiality one needs to demonstrate that public discussion integrates social actors in transactions and also in the consequences of decisions.